Atherosclerosis: immunopathogenesis and strategies for immunotherapy (2021)
Atherosclerosis, a chronic inflammatory condition in which atheroma accumulates within the intima of the arterial wall, is a life-threatening manifestation of cardiovascular disease, due to atheroma rupture, chronic luminal narrowing and thrombosis. Current knowledge of the role of a protective immune response in atherosclerotic lesions has provided promising opportunities to develop new immunotherapeutic strategies. In particular, Tregs exert an atheroprotective role by releasing anti-inflammatory cytokines (IL-10/TGF-β) and suppressing autoreactive T lymphocytes. In vivo animal experiments have shown that this can be achieved by developing vaccines that stimulate immunological tolerance to atheroma antigens. Here, we present an overview of the current knowledge of the proatherogenic immune response, and we discuss the strategies currently used as immunoregulatory therapy. Lay abstract: Atherosclerosis is a chronic inflammatory disease in which the wall of the artery develops abnormalities, and can lead to serious problems, including heart attack, stroke, or even death. Scientific evidence has shown that the immune system is involved in the development and progression of atherosclerosis. Understanding the role of protective immune response in atherosclerosis provided promising opportunities to develop approaches for prevention and treatment.